Relapse prevention with antidepressant drug treatment in depressive disorders: a systematic review. - Geddes, J; Carney, S; Davies, C; Furukawa, T; Kupfer, D; Frank, E; Goodwin, G (2003)
BACKGROUND: Antidepressant drugs can promote remission from acute depressive episodes. Our aim was to establish how long such treatments should be continued to prevent relapse. METHOD: We did a systematic overview of evidence from randomised trials of continuing treatment with antidepressants in patients with depressive disorders who have responded to acute treatment. Medline, Embase, Cinahl, PsycLIT, Psyndex, and Lilacs were searched. FINDINGS: Data were pooled from 31 randomised trials (4410 participants). Continuing treatment with antidepressants reduced the odds of relapse by 70% (95% CI 62-78; 2p<0.00001) compared with treatment discontinuation. The average rate of relapse on placebo was 41% compared with 18% on active treatment. The treatment effect seemed to persist for up to 36 months, although most trials were of 12 months' duration, and so the evidence on longer-term treatment requires confirmation. Significantly more participants allocated antidepressants withdrew from the trials than did those allocated to placebo (18% vs 15%, respectively; odds ratio 1.30, 95% CI 1.07-1.59): the treatment effect could be even greater in adherent patients. The two-thirds reduction in risk of depressive relapse seemed to be largely independent of the underlying risk of relapse, the duration of treatment before randomisation, or the duration of the randomly allocated therapy. INTERPRETATION: Antidepressants reduce the risk of relapse in depressive disorder, and continued treatment with antidepressants would benefit many patients with recurrent depressive disorder. The treatment benefit for an individual patient will depend on their absolute risk of relapse with greater absolute benefits in those at higher risk. Further trials are needed to establish the optimum length of therapy and should include patients who were not well represented in these trials, including those at low risk of relapse.